Does Auditor Experience, Auditor Work Stress, And Time Budget Pressure Affect Audit Quality? - Mahmudi, Mahmudi; Safira, Satyarani; Aisyah, Maulidyati (Adpebi Science Series, 2022)
The purpose of this study is to analyze the effect of auditor experience, auditor work stress, and time budget pressure toward audit quality. The sample of this research were auditors who work as the Supreme Audit Board of The Republic of Indonesia (BPK) representative in The Special Region of Yogyakarta. This study employed multiple regression analysis to test the hypotheses proposed. The results of this study found that auditor experience has a positive and significant effect toward audit quality. Meanwhile, auditor work stress and time budget pressure have negative and significant effect toward audit quality. The implication of this study is discussed.